The diversity of Escherichia coli infections - Donnenberg, Michael (Henry Stewart Talks, 2009)
How can E. coli cause so many diseases?, Different E. coli strains, ExPEC, UPEC pathogenesis and virulence factors, ExPEC gene discovery, ETEC and EPEC disease, The bundle forming pilus, BFP biogenesis, Bundlin, The locus of enterocyte effacement, Intimin, The translocon, EHEC clinical features, Shiga toxins, Do antibiotics increase HUS risk?, EHEC diagnosis, therapy and prevention, EAEC pathogenesis, Relationships among pathogenic E. coli